Promotion and Service as Strategic Marketing Tools towards Islamic House Financing - Abd Aziz, Noriza; Abu Bakar, Azizi; Isa, Mohamad Yazid; Abdul Aziz, Ibrahim (Institute of Advanced Scientific Research, 2019)
This paper focused on the effect of promotion and service as strategic marketing tools that influence customers’ selection towards Islamic house financing. The findings revealed that the levels of satisfaction in promotion and service among customers were positive. The findings from the study can give impact and implication to bank marketers to understand the salient criteria used by customers in choosing Islamic house financing. It should help those banks which operate in a dual-banking system to develop human capital with sufficient appropriate knowledge and skills, and to equip themselves with engineered market segmentations and targeted marketing strategies